2019
DOI: 10.1101/784199
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of the lymphangioleiomyomatosis cell and its uterine origin

Abstract: Lymphangioleiomyomatosis (LAM) is a metastasizing neoplasm of reproductive age women that causes cystic lung remodeling and progressive respiratory failure. The source of LAM cells that invade the lung and the reasons that LAM targets women have remained elusive. We employed single cell and single nuclei RNA sequencing on LAM lesions within explanted LAM lungs, known to contain smooth muscle like cells bearing mTOR activating mutations in TSC1 or TSC2, and identified a unique population of cells that were read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…These include alternative blood-based biomarkers [73] and improved use of CT imaging technology to determine progressive disease in those with normal spirometry [74,75]. Recent studies have identified that that LAM cells probably originate in the uterus and specific proteins associated with this may be novel biomarkers [76]. These continued advances in understanding the molecular pathogenesis will potentially identify better therapeutic options and reveal more robust clinically meaningful biomarkers.…”
Section: Future Directionsmentioning
confidence: 99%
“…These include alternative blood-based biomarkers [73] and improved use of CT imaging technology to determine progressive disease in those with normal spirometry [74,75]. Recent studies have identified that that LAM cells probably originate in the uterus and specific proteins associated with this may be novel biomarkers [76]. These continued advances in understanding the molecular pathogenesis will potentially identify better therapeutic options and reveal more robust clinically meaningful biomarkers.…”
Section: Future Directionsmentioning
confidence: 99%
“…1J, right panel). We next examined the overlap of these DEGs with a recently published LAM gene signature derived from single cell RNA-seq profiling of primary lesions (24). We observed that both DEG lists overlap substantially (65.8% of the total 760 LAM genes) and share both common and distinct genes with the LAM gene signature (Fig.…”
Section: Loss Of Tsc2 and Hydrogel Culture Both Confer Transcriptomic Features Of Lammentioning
confidence: 94%
“…S1I-J). Both DEG lists ranked "extracellular matrix organization" as most highly enriched, which is also the top enriched term in a primary LAM lesion gene signature list (24). The DEGs distinguishing genotype were also enriched in many terms related to development, similar to primary LAM lesions (24).…”
Section: Loss Of Tsc2 and Hydrogel Culture Both Confer Transcriptomic Features Of Lammentioning
confidence: 96%